Problems on the teaching of geometry in comprehensive schools for 21st century - Dagienė, Valentina (Lietuvos matematikos rinkinys, 2001)
The main aim of this paper is to identify current major trends in geometry and to discuss perspectives concerning its teaching in schools, for today and for tomorrow. Geometry involves three kinds of cognitive processes which fulfill specific epistemological functions: (1) visualization processes with regard to space representation for the illustration of a statement, for the heuristic exploration of a complex situation, etc.; (2) construction processes by tools: construction of figurations can work like a model; (3) reasoning in relationship to discursive processes for extension of knowledge, for proof, for explanation. The paper deals with relationship between geometry and computer technology. Among all school subjects, geometry stands as one which is bound to be influenced most profoundly by the recent progress both in hardware and software development. The purpose is to examine some influence of computer technology in the teaching and learning of geometry.